An Assessmenst Of Cost And Time Value In The Fresh Produce Supply Chain - Li, Dongchan (2010)
Nowadays, supply chain management (SCM) is considered as the key to win the business competition. It can bring many benefits for companies, such as waste elimination, increasing efficiency and customers‘ satisfaction. However, unnecessary waste still exists. In order to handle the issue better, a clear view of the sources of waste is required. Hence, the visibility of supply chain in terms of time and cost becomes more and more demanding. This research investigates the relevant issues of the fresh produce supply chain based on a case study in an international food company called Malaysian Agrifood Corporation Berhad (MAFC). It explores the issues of time and cost management within tomato supply chain over a three-month period. It examines all processes and stages of material and information flows along the Lushious tomato supply chain, aiming at highlighting the level of time and cost consumed by different processes across the supply chain and hence to unveil the waste areas. Based on these objectives, SCTCM (Supply Chain Time and Cost Mapping) is employed for supply chain analysis. This paper will demonstrate the application of SCTCM, which can lead to substantial time and cost savings. The results indicate that analyzing supply chains with time and cost tools simultaneously is fundamental for managers to make better decisions. This paper argues that better visibility of supply chain can be achieved through investigating supply chains with time and cost tools simultaneously. Analysis of time and cost consumed at each activity can provide some insights for managers to make better decisions.